Reforma al art.187 del Código Orgánico Integral Penal, en cuanto al abuso de confianza - Granda Valdivieso, Diana Carolina (2015)
The core budget of the offence of breach of trust, is the provision which makes the active subject for himself or for another, of a movable thing outside, same which transmitted to it holding and not the domain to the detriment of the liability. Now, the scope of the word transmission implies a transfer of rights, which means that transmission holding concerning the crime of abuse of trust as budget it is, the thing is transferred material and physically under any title allowed by law. The Constitution of the Republic in its paragraph Art.66 22 mentions the right to property, determining the following: "26. The right to the property in all its forms, with function and social and environmental responsibility. The right of access to the property will be effective with the adoption of public policies, among other measures." This constitutional treatment of property does not entail a simple point of order, but it can be deduced the doctrine that presents the Constitution with regard to this right. Indeed, the Constitution conceives of the property as a "civil right", from the level of the individual, and is a means to achieve the full development of the moral and material of the person. Meanwhile, the Art.187 establishes: that; "The person who has for itself or a third, of money, goods or assets delivered with the condition of restoring them or use them in a particular way, shall be punished with imprisonment of one to three years. The same penalty is imposed on the person who, abusing another, signed in blank document, extend it any document to the detriment of the signer or a third." In law, the abuse of trust is an offence where the offender abused the trust placed by the victim. One of the most common abuses of trust is the misappropriation of assets, taking advantage of that victim grants you the use or possession of said well. The legal problem lies in the second paragraph of this article, since in contrast to the first paragraph, is determined the abuse of signature on a document on a person in favor of another third target, since they are different acts and they should not be punished in the same way, since this latest act has and brings more serious repercussions, which fall within the rights of property of the victim or abused Hence the urgent need to carry out a study and research on the present issue, in order to determine the legal reform immediately to the Art.187 of the organic comprehensive Penal Code regarding the abuse of trust